Early Letters of George Wm. Curtis to John S. Dwight; Brook Farm and Concord - Curtis, George William, 1824-1892; Cooke, George Willis, 1848-1923 (Salt Lake City, UT : Project Gutenberg, 2005)
"Early Letters of George Wm. Curtis to John S. Dwight: Brook Farm and Concord" edited by George Willis Cooke is a collection of correspondence from the early 19th century. The letters provide insights into the lives and thoughts of George William Curtis and his brother Burrill during their formative years at Brook Farm, an experiment in communal living and transcendental philosophy, as well as their interactions with influential figures like Ralph Waldo Emerson and John S. Dwight. At the start of this compilation, the reader is introduced to Curtis's background, including his education and the strong bond with his brother, as well as their admiration for Emerson. The letters explore Curtis's feelings and experiences while attending the Brook Farm community, highlighting interactions with various residents, the nature of their education, and their participation in the society$1 (Bs unique blend of labor, study, and cultural activities. Curtis$1 (Bs initial enthusiasm for the transcendentalist ideas and the vibrant social life at Brook Farm is evident; however, he also maintains a degree of critical distance from some of the community's ideals, indicating a nuanced perspective on the experiment. This opening portion lays the groundwork for understanding not only Curtis$1 (Bs personal journey but also the broader cultural and intellectual currents of his time. (This is an automatically generated summary.)s
Release date is 2005-06-01
Produced by Eric Eldred, Beth Trapaga and the Online Distributed Proofreading Team
Keywords: Authors, American -- 19th century -- Correspondence; Brook Farm Phalanx (West Roxbury, Boston, Mass.); Curtis, George William, 1824-1892 -- Correspondence; Dwight, John Sullivan, 1813-1893 -- Correspondence